Effect of Methadone Maintenance Therapy on Anthropometric Indices in Opioid Dependent Patients - Montazerifar, Farzaneh (Kowsar, 2012)
BACKGROUND: Opium abuse significantly affects the nutritional status of users and frequently leads to undernourishment. Methadone maintenance therapy has been used as one of the possible ways to prevent of infection diseases such as HIV and hepatitis B and C and improve the quality of life in opioid-dependent patients. OBJECTIVES: The aim of this study was to assess the anthropometric and socio-demographic characteristics of opium addicted persons before and after 8 weeks of methadone maintenance therapy (MMT). PATIENTS AND METHODS: A clinical cross-sectional study was carried out on 55 opium users (15 women and 40 men; mean aged 31.6 ± 10 years), dependent on opium and its derivatives at the Addiction Treatment Clinic of the Baharan psychiatric Hospital, Zahedan, Sistan and Baluchistan Province, Iran, in 2011. The patients were examined before and after 8 weeks MMT. Weight and height of participants were taken and the body mass index (BMI) was calculated. RESULTS: Body weight increased significantly from 61.4 ± 14.4 to 65.3 ± 14.2 kg and BMI from 21.4 ± 4.2 to 23 ± 5.6 (kg/m(2)) after 8 weeks of methadone maintenance therapy in opium users (P < 0.01). The percentages of underweight, overweight and obese patients were; 27.3%, 18.2% and 3.6%, respectively pre-MMT, and 12.7%, 18.2% and 7.2%, respectively after MMT. CONCLUSIONS: The study shows that methadone Maintenance Therapy led to improvements in nutritional status.